Estimation of frequency characteristics of photodiode determined by motion of charge carriers in the space-charge region - Danilyuk, A.I.; Dobrovolskiy, Yu.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Frequency characteristics of photodiode determined by motion of charge carriers in the space-charge region was estimated. It was shown that the current in the external circuit depends on two functions (their specific kind) of coordinates of the electric field and generation density of photodetector current.